Unlocking the Nootropic Effect of Trachyspermum ammi Seeds against Scopolamine-induced Memory Deficits in Rodents - Muhammad Ali Rajput; Ahmed, Mohammad Mesbahuzzaman; Pallav Sengupta; Azra Batool; Saeed Ahmed Lakho; Salman Ahmed; Ahmed, Zeeshan (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To evaluate the potential of TASE in improving memory and cognitive function using animal models. METHODOLOGY: These experimental trials were conducted in the Pharmacology Laboratory, University of Karachi, from January - November 2021. Thirty-five male Wistar Rats and thirty-five male mice weighing 200-230g and 20-40g, respectively, were used for Morris water maze (MWM) and passive avoidance response (PAR) tests. The subjects were distributed equally into five groups. Group 1 (control) received 2% gum tragacanth, Groups 2, 3, and 4 received TASE at 50, 100, and 250mg/kg, respectively, and Group 5 received Piracetam at 200mg/kg. Scopolamine at 0.4mg/kg was administered intraperitoneally to induce amnesia in rodents. RESULTS: In the MWM test, TASE at 250 and 100mg/kg significantly decreased the escape latency in rats compared to the control group. Similarly, in the PAR test, TASE at 250 and 100mg/kg significantly delayed the compartment change time in mice compared to the control group. The outcomes of both experiments were comparable to the reference drug Piracetam, indicating that TASE improves cognition and has substantial potential as an anti-amnesic agent. This potential may be due to the presence of significant phytochemicals in TASE, such as Thymol, saponins, flavonoids, ?- and ?-pinene, and ?-terpinene, which improve cholinergic neurotransmission and exert antioxidant effects. CONCLUSION: TASE improves memory and cognitive function, likely due to its significant phytochemical content. Identifying these nutritional elements is crucial for researching and developing innovative and potent medications.